2022
DOI: 10.1177/03635465221108195
|View full text |Cite
|
Sign up to set email alerts
|

The Vascularization Course of Labral Autograft and Its Effect on Tissue Healing: Acetabular Labral Augmentation Versus Labral Reconstruction in a Porcine Model

Abstract: Background: The preservation of the native labral vascularization is assumed to be the potential advantage of acetabular labral augmentation, the effect of which remains unknown. Purpose: To identify the vascular distribution within the labral autograft and its effect on the healing process between labral augmentation (AUG) and reconstruction (RECON) in a porcine model. Study Design: Controlled laboratory study. Methods: A total of 36 pigs randomly underwent unilateral labral augmentation or reconstruction (AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Second, we did not explore the effect of different graft materials on tissue healing. In a prior cadaveric study 19 , we found that the porcine tensor fasciae latae was too thin to be tubularized. In contrast, we found that the initial tubular shape and sufficient volume of the Achilles autograft made it a suitable option, and no related complications occurred in the present study.…”
Section: Limitationsmentioning
confidence: 83%
See 2 more Smart Citations
“…Second, we did not explore the effect of different graft materials on tissue healing. In a prior cadaveric study 19 , we found that the porcine tensor fasciae latae was too thin to be tubularized. In contrast, we found that the initial tubular shape and sufficient volume of the Achilles autograft made it a suitable option, and no related complications occurred in the present study.…”
Section: Limitationsmentioning
confidence: 83%
“…Based on a previous study that included histological analysis 19 , the desired sample size for 2-sample t tests was calculated (PASS version 15; NCSS) with a error = 0.05 and power = 0.8. Continuous variables were expressed as the mean and 95% confidence interval (CI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,15,22,23,31 However, our previous results have shown that poor tissue healing occurred because of the slow and insufficient vascular ingrowth within the articular half of the reconstructed autograft. 25 Given that, this study aimed to explore the possibility of improving the vascularization of the inner half through bone marrow stimulation and to find out whether the volume of the regrown tissue is sufficient to fill the labral defect after microfracture at the bony rim of the acetabulum. Through penetrating the subchondral plate, a biological response for tissue repair is stimulated within the formed marrow clot, which provides an environment for mesenchymal stem cells to differentiate and finally mature into a fibrous repair matrix.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,22,23,31 However, our previous results have shown that poor tissue healing occurred because of the slow and insufficient vascular ingrowth within the articular half of the reconstructed autograft. 25 Given that, this study aimed to explore the possibility of improving the vascularization of the inner half through bone marrow stimulation and to find out whether the volume of the regrown tissue is sufficient to fill the labral defect after microfracture at the bony rim of the acetabulum.…”
Section: Discussionmentioning
confidence: 99%